2019
DOI: 10.1039/c9ra05110d
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids strongly affect the interaction of bacteria with magnesium oxide and silica nanoparticles

Abstract: The antibacterial properties of nanoparticles can be strongly affected by interactions with ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…However, silica probably served as a scaffold for this process that could be observed in the microscopic analysis ( Figure 3 ). A similar effect was observed by Borkowski et al [ 37 ], who detected the increased interaction of cells with silica nanoparticles in the presence of positively charged ionic liquids. The role of silica in our studies can also be supported by the fact that we did not observe such a strong agglomeration effect in the additional samples that contained only TiO 2 .…”
Section: Discussionsupporting
confidence: 86%
“…However, silica probably served as a scaffold for this process that could be observed in the microscopic analysis ( Figure 3 ). A similar effect was observed by Borkowski et al [ 37 ], who detected the increased interaction of cells with silica nanoparticles in the presence of positively charged ionic liquids. The role of silica in our studies can also be supported by the fact that we did not observe such a strong agglomeration effect in the additional samples that contained only TiO 2 .…”
Section: Discussionsupporting
confidence: 86%
“…The examples from the literature concern the lower activity of DEH in P. aeruginosa and S. aureus treated with Ag-NPs [35], a stimulation of the DEH activity in E. coli and B. cereus using SiC nanofibers as well as the inhibition of this enzyme in B. cereus using SiC/Ag/CE/T [21]. In another study, Borkowski et al [36] reported that MgO-NPs strongly stimulated the DEH activity in E. coli and B. cereus, while SiO 2 -NPs only affected the E. coli enzymes. The provided examples clearly indicate the diverse impact of tested NMs on various bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic activity of the bacteria was determined based on the dehydrogenases activity using the method previously successfully tested and reported by Borkowski et al [ 25 ]. In the experiment, the 12-h cultures of E. coli and B. cereus bacteria with the growth densities of 0.594 and 1.24 equal to 227 µg of protein mL −1 and 230 µg of protein mL −1 , respectively, were used.…”
Section: Methodsmentioning
confidence: 99%